Perceptions of Ecuadorian indigenous healers on their relationship with the formal health care system: barriers and opportunities - Estefanía Bautista-Valarezo; Víctor Duque; Veronique Verhoeven; Jorge Mejia Chicaiza; Kristin Hendrickx; Ruth Maldonado-Rengel; Nele R.M. Michels (BMC, 2021)
Abstract Background The new paradigm of intercultural policies focuses on rethinking the common public culture. In Ecuador, the "Buen Vivir" plan seeks to incorporate the ancestral medical knowledge, experience and beliefs of traditional healers into the formal health services. This study explores views on the formal health system from the perspective of the healers belonging to the Kichwa and Shuar ethnicities in the South of Ecuador. Methods A qualitative study with a phenomenological approach was performed. Focus groups were conducted in three locations in Southern Ecuador. Shuar, Kichwa and Mestizo ethnic groups were included in the research. Results Eleven focus groups with a total of 110 participants belonging to the Shuar, Kichwa and Mestizo ethnic groups participated in the study. Six themes were created through analysis: 1) conflicts with health professionals, 2) acceptance of traditional healers, 3) respect, 4) work as a team, 5) environment and patient care, and 6) salary and recognition. Conclusion This study indicated the perceived barriers compromising respectful collaboration between health staff and traditional healers from an indigenous perspective. Power inequalities and a historically unidirectional relationship and, in addition, differences in health beliefs, seem to create misunderstandings regarding each other's approach when faced with health and disease. However, insight in these barriers can create opportunities towards collaboration, which will have a positive effect on patient confidence in one or both systems and support continuity between traditional healers and the formal health system.